Model independent expansion history from supernovae: Cosmology versus systematics - L'Huillier, Benjamin; Shafieloo, Arman; Linder, Eric V.; Kim, Alex G. (NURIS; Energetic Cosmos Laboratory, 2019)
We examine the Pantheon supernovae distance data compilation in a model independent analysis to test the validity of cosmic history reconstructions beyond the concordance ΛCDM cosmology. Strong deviations are allowed by the data at z≳1 in the reconstructed Hubble parameter, Om diagnostic, and dark energy equation of state. We explore three interpretations: 1) possibility of the true cosmology being far from ΛCDM, 2) supernovae property evolution, and 3) survey selection effects.
Energetic Cosmos Laboratory. ECL Publication, 2019
Keywords: The 2nd international conference of the Energetic Cosmos Laboratory (ECL); Energetic Cosmos Laboratory (ECL); ECL19